1970
DOI: 10.1136/hrt.32.6.795
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac lesions in fatal cases of recent myocardial ischaemia from a coronary care unit.

Abstract: In IOO consecutive deaths from a coronary care unit, the coronary arteries were examined microscopically in longitudinal sections (serial and semi-serial) so that the entire extramural part of each artery was scrutinized. Occluded coronary arteries were found in 88 cases, the occlusions being due to thrombi in 17, to the contents of soft atheromatous plaques in 22, and to a mixture of soft plaque content and thrombus in 49; thus in 7I cases the coronary occlusions are due basically to the rupture of soft plaqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1972
1972
1992
1992

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…By contrast, Bouch and Montgomery (1970) then reported that in 100 consecutive patients dying from myocardial ischaemia, occluded coronary arteries were found in 88 (88%), and stated that this contradiction of previous results was largely attributable to alterations of technique. In addition, they believed that case selection might have played a part.…”
Section: (1) Relation Between Coronary Thrombus and Acute Myocardial mentioning
confidence: 87%
“…By contrast, Bouch and Montgomery (1970) then reported that in 100 consecutive patients dying from myocardial ischaemia, occluded coronary arteries were found in 88 (88%), and stated that this contradiction of previous results was largely attributable to alterations of technique. In addition, they believed that case selection might have played a part.…”
Section: (1) Relation Between Coronary Thrombus and Acute Myocardial mentioning
confidence: 87%
“…9 " 12 The initiating event for the development of ischemia appears to be plaque rupture, the pathogenetic mechanism of which remains largely unexplained. 10 Plaque rupture initially causes platelet aggregation and subsequently leads to thrombus formation.…”
Section: Discussionmentioning
confidence: 99%
“…These observations emphasise the importance of distinguishing between " hard " and " soft '' atherosclerotic plaques (Montgomery, 1959;Bouch and Montgomery, 1970;Prathap, 1973b). Healing of mural thrombi in systemic arteries leads to relatively stable hard fibromuscular plaques.…”
Section: Discussionmentioning
confidence: 96%